Wolfhart Pannenberg on human destiny - Wong, Kam Ming (Ashgate new critical thinking in religion, theology, and biblical studies series, 2016)
Setting the scene -- Image of God as both fount and destiny of humanity -- Openness of humanity -- Sin as an antithesis to human destiny -- Eschatology and ethics in human destiny -- Theological anthropology : destiny centred, history focused